Building Bonds, Healing Youth: Prioritizing Youth Critical Consciousness Development in CBPR - Briana Woods-Jaeger; Paige O'Connor; Teesha Miller; Chakilah Wade; D'Marko Price; Briana Boykin; Kelsey Christensen; Jannette Berkley-Patton (Journal of Participatory Research Methods)
Community violence continues to be a major national public health issue that disproportionately impacts African American youth. Community Based Participatory Research (CBPR) approaches have been recommended to address youth violence and provide an opportunity to partner in research with those most impacted to develop new strategies. In this brief report we describe specific capacity building efforts in our CBPR project, Building Bonds, Healing Youth, which aims to develop and test a community-level intervention to promote resilience among African American youth exposed to community violence. We specifically describe our capacity building efforts that centered around developing youth critical consciousness and highlight specific methods that we employed. Reflections from our youth partners highlight the potential impact of incorporating youth critical consciousness development into capacity building efforts with youth partners. This brief report supports incorporating critical consciousness in CBPR with youth to promote mutual benefit as youth contribute their lived experiences, expertise, and commitment to improving research addressing youth health and well-being.